Francesca Gargallo, Marcha seca (Era, México D.F, 1999, pp. 76, ISBN 968-411-454-0) (Altre Modernità, 2009)
Francesca Gargallo, Marcha seca (Era, México D.F, 1999, pp. 76, ISBN 968-411-454-0)por Cristina Ponisio